6-6x=5x-9x-2x

Simple and best practice solution for 6-6x=5x-9x-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-6x=5x-9x-2x equation:


Simplifying
6 + -6x = 5x + -9x + -2x

Combine like terms: 5x + -9x = -4x
6 + -6x = -4x + -2x

Combine like terms: -4x + -2x = -6x
6 + -6x = -6x

Add '6x' to each side of the equation.
6 + -6x + 6x = -6x + 6x

Combine like terms: -6x + 6x = 0
6 + 0 = -6x + 6x
6 = -6x + 6x

Combine like terms: -6x + 6x = 0
6 = 0

Solving
6 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8x/7-3/4=6/2-4x/4 | | 3x+-3=180 | | (2x+4)(x+4)=196+3x | | 10m+6=6m+30 | | x-15=x/77 | | -4p-12=12 | | w+2.9=6.4 | | z^2=-2z-14 | | -3/8t=1/6 | | y=20-3(1) | | g=y-cx | | 8(3n+3)=8(6n+3)+2 | | 3(1.5x+9)= | | 2(3x-2)=3(4x+5)+7X | | 144x=3268.80 | | 5x-12+x=-13 | | 4/3x3.14x3.04^3 | | -4p+8(p+3)=4(p-8)+2 | | 6(x+4)-3x=11 | | f(2.5)=2x^2-3+7 | | (4x-15)+(5x+11)+(5x+5)+(6x+19)=360 | | -6.5-4x-1.6-3x=-6+9.8 | | 7(x^2)-2=5x | | 8xt=32 | | 2(5x+4)-2(9x+2)= | | 7n-(1+7n)=3(n-7)-7n | | 72x(3/2)n | | 30x^2-114x+108=0 | | n+9=25 | | 19h+1.50=15+2.75 | | (X-5)/4=-20 | | 3(w-2)-2=8-(w+4) |

Equations solver categories